A new electrophysiologic triad for identification and localization of the critical isthmus in atrial flutter - Pedro Adragão; Daniel Matos; Francisco Moscoso Costa; Pedro Carmo; Diogo Cavaco; Gustavo Rodrigues; João Carmo; Francisco Morgado; Miguel Mendes (Revista Portuguesa de Cardiologia, 2020)
Introduction: Atypical atrial flutter (AFL) is a supraventricular arrhythmia that can be treated with catheter ablation. However, this strategy yields suboptimal results and the best approach is yet to be defined. Carto® electroanatomical mapping (EAM) version 7 displays a histogram of the local activation times (LAT) of the tachycardia cycle length (TCL), in addition to activation and voltage maps. Using these EAM tools, the study aimed to assess the ability of an electrophysiologic triad to identify and localize the critical isthmus in AFL. Methods: Retrospective analysis using Carto® EAM of a single center registry of individuals who underwent left AFL ablation over one year. Subjects with non-left AFL, no high-density EAM, under 2000 points or no left atrium wall or structure mapping were excluded. Sites where arrhythmia is terminated via ablation were compared to an electrophysiologic triad comprising areas of low-voltage (0.05 to 0.3 mV), deep histogram valleys (LAT-valleys) with less than 20% density points relative to the highest density zone and a prolonged LAT-valley duration, which included 10% or more of the TCL. The longest LAT-valley was designated as the primary valley, while additional valleys were named as secondary. Results: A total of nine subjects (six men, median age 75, interquartile range 71-76 years) were included. All patients presented with left AFL and 66% had a history of ablation for atrial fibrillation and/or flutter. The median TCL and collected points were 254 ms (220-290) and 3300 (IQR 2410-3926) points, respectively. All individuals with AFL presented with at least one LAT-valley on the analyzed histograms, which corresponded to heterogeneous low voltage areas (0.05 to 0.3 mV) and affected more than 10% of TCL. Six of the nine patients presented with a secondary LAT-valley. All arrhythmias were terminated successfully following radiofrequency ablation at the primary LAT-valley location. After a minimum three-month follow-up all patients remained in sinus rhythm. Conclusion: An electrophysiologic triad identified the critical isthmus in AFL for all patients. Further studies are needed to assess the usefulness of this algorithm in improving catheter ablation outcomes. Resumo: Introdução: O flutter auricular atípico (FLA) é uma arritmia supraventricular que pode ser alvo de tratamento por ablação com cateter. No entanto, a melhor abordagem ainda não foi definida e esta estratégia apresenta resultados subótimos. O sistema de mapeamento eletroanatómico (MEA) Carto® versão 7.0 dispõe, para além dos mapas de voltagem e ativação, de um histograma dos tempos de ativação local (TAL) do ciclo do FLA. Usando esta tecnologia de MEA, o estudo tem como objetivo avaliar a capacidade de uma tríade eletrofisiológica para identificar e localizar o istmo crítico do FLA. Métodos: Análise retrospetiva de um registo unicêntrico de doentes submetidos a ablação de FLA esquerdo durante um período de em ano e MEA com Carto®. Foram excluídos todos os doentes com FLA não esquerdo, ausência de MEA de alta densidade, aquisição de menos de 2000 pontos ou falta de mapeamento em qualquer parede ou estrutura da aurícula esquerda. Os locais de ablação nos quais houve supressão das arritmias foram comparados com uma tríade eletrofisiológica constituída por: zonas de baixa voltagem (0,05 até 0,3 mV), locais de vales profundos do histograma com menos de 20% da densidade de pontos do MEA relativamente à zona de maior densidade e um vale prolongado com 10% ou mais do ciclo taquicardia. O vale do TAL mais longo foi designado como vale primário, enquanto vales adicionais foram nomeados como secundários. Resultados: Foram incluídos nove doentes (seis homens, mediana de 75 anos IQR 71-76 anos) foram incluídos. Todos os doentes apresentaram FLA esquerdo e 66% tinham sido sujeitos previamente a ablação de fibrilhação e/ou flutter auricular. O ciclo mediano da taquicardia e o número mediano de pontos adquiridos foram respetivamente de 254 (220-290) milissegundos e 3300 (IQR 2410-3926) pontos. Os FLA apresentaram pelo menos um vale primário nos histogramas analisados, correspondendo a áreas heterogéneas de baixa voltagem (0,05 a 0,3 mV) e contendo mais de 10% do ciclo da taquicardia. Seis dos nove doentes apresentavam vales de TAL secundários. Os FLA foram efetivamente tratados no vale primário por ablação com radiofrequência. Após um seguimento de pelo menos três meses, os doentes permaneciam em ritmo sinusal. Conclusão: Uma tríade eletrofisiológica permitiu a identificação do istmo crítico em todos os doentes. São necessários mais estudos para avaliar o valor deste algoritmo para melhorar os resultados da ablação por cateter.